Impact of surgically placed radiopaque markers during aortic root surgery on facilitating secondary diagnostic and therapeutic interventions - Emmanuel Zimmer; Maria Nucera; Clarence Pingpoh; Murat Yildiz; Paul Puiu; Florian Schoenhoff; Martin Czerny; Matthias Siepe (Journal of Cardiothoracic Surgery, 2023)
Abstract Background Implantation of radiopaque markers during aortic root surgery might possibly facilitate upcoming coronary angiography or transcatheter aortic valve implantation. Aim of this study was to report the impact of surgically placed radiopaque markers on procedural characteristics and on angiographic outcomes. Methods We retrospectively analyzed baseline characteristics, preoperative and postoperative data as well as procedural findings. In addition, a subgroup analysis of all patients who underwent coronary angiography after aortic root surgery was performed to report radiation time and contrast media used. Results A total of 469 patients underwent aortic root surgery between January 2008 and April 2020. Patients were divided into two groups: group w/ markers (n = 182) and group w/o markers (n = 287). A propensity score matching was performed resulting in a total of 28 patients w/ markers and 28 patients w/o markers. Aortic cross-clamp time did not differ statistically significantly between the group w/o markers and the group w/ markers (124.0 [96.0–150.0] versus 123.0 [110.0–149.0] min, p = 0.09). There was no increased probability for requirement of postoperative angiography in the group w/o markers compared to the group w/ markers (11.8% versus 15.4%, p = 0.27). There was no statistically significant difference in the radiation time 5.5 [3–6.5] versus 5 [2.5–7.5] min, p = 0.62) nor in the amount of contrast media used (85 [77.5–100] versus 80 [60–90] ml, p = 0.07). Conclusions Surgically placed radiopaque markers during aortic root surgery do not increase operative risk and have the potential for facilitating secondary diagnostic and therapeutic interventions.